Science Literacy and Climate Change Issues in Elementary School Science Learning as a Green Education Effort - Sutra Awaliyah Darfin; Umi Nur Kholifatun; Harpina Harpina (FKIP UNSULTRA, 2025)
Science education at the elementary school level (SD) has a strategic role in instilling scientific literacy and environmental awareness from an early age. Amid the increasing global issues related to climate change, it is important for students to understand science not only as a collection of concepts, but also as a tool for critical thinking about natural and social phenomena that have an impact on the sustainability of life. This literature study aims to examine the contribution of Natural Science (IPA) learning in building scientific literacy and increasing awareness of climate change issues in elementary school students as part of the implementation of Green Education. The method used is a literature study by reviewing various sources of scientific journals, articles, and relevant publications in the last five years (2019–2024). The results of the study show that scientific literacy developed through environmental-based science learning can improve students' understanding of the concept of climate change, encourage environmental awareness, and shape environmentally friendly behavior. The integration of current issues such as global warming, pollution, and nature conservation in science learning has also proven effective in building students' cognitive, affective, and psychomotor dimensions. Thus, scientific literacy is an important foundation in forming a young generation who are aware of the importance of environmental sustainability and play an active role in nature conservation.